The Analysis of Translation Shift of English Noun Phrases in Edgar Allan Poe’s “The Black Cat” Into Indonesian - Novi Napila Pajariah Pajariah (Passage, 2014)
This research investigates the translation shifts of English noun phrases in the short story entitled “The Black Cat” (1843) by Edgar Allan Poe into Indonesian as “Kucing Hitam” (2010) which was translated by Maggie Tiojakien. It was focused on the types of translation shifts and the change of meaning in the translation shifts. This research was mostly qualitative supported by descriptive quantification. The data were obtained from an online source at http://pinkmonkey.com/dl/library1/cat_.pdf and from anthology entitled Kisah-kisah Tengah Malam which was published by PT Gramedia Pustaka Utama in 2010. The data were analyzed by applying translation shift theory proposed by Catford (1965) and supported by Fabb’s (2005) Tree Diagram as a tool. The result showed that the most frequent shift that was used by translator was structure shift (59%). It was because the differences of grammatical structure between English and Indonesian. Besides, the change of meaning mostly took place in implicitation (34,4%). It means that the translator tends to use the words in the target language text with words having more general meaning than the source language text in order to fit the context of the story.Keywords: Translation Shift, Noun Phrases, Change Of Meaning